Fiscal Revenues in South Mediterranean Arab Countries Vulnerabilities and Growth Potential - Nashashibi, Karim A. (International Monetary Fund, 2002)
This paper reviews the fiscal revenue performance of Southern Mediterranean Arab countries (SMCs) over the last decade and compares this performance with selected middle income and Organization for Economic Cooperation and Development (OECD) countries. These revenues have been declining over the past few years, and this trend is expected to continue because of a fall in mineral receipts and trade liberalization. Individual income tax yields are substantially lower than in other regions but the introduction of the value-added tax has proven to be highly successful. Higher trade protection than in other regions must be reduced, if SMCs are to be integrated into the global economy. Loss of nontax and customs revenues can be offset by reforms in income tax systems, petroleum product pricing, and by ensuring, through flexible exchange rate policies, that competitiveness is maintained